PENGGUNAAN MEDIA KONKRET RODA PINTAR UNTUK MENINGKATKAN KETERAMPILAN MENULIS PERMULAAN SISWA KELAS 1 SEKOLAH DASAR - Frandhica Wahyu Ardhianto; Hendratno; Heru Subrata (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to improve the writing skills of students in elementary school through the use of smart wheel media. The focus of this research is to develop a syllable that focused in smart wheel learning media for the first grade students in elementary school. The method used in this research is the SLR (Systematic Literature Review) method. By applying the SLR method, the researcher will identify, analyze, evaluate, and interpret all existing research. The researcher will conduct a systematic review of the journals that have been collected. The data that included in this literature review is an analysis of the summaries of several documented articles on improving students' writing skills through the learning media. Based on the research results from 2017 to 2024, the use of smart wheel media showed positive results in improving student's early writing skills. Students tend to enjoy the learning process more when the media is used. The smart wheel media also attracts student's attention to more understanding the syllable arrangement presented